2017
DOI: 10.3390/su9101717
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Environmental Accounting and Reporting Practices of Listed Banking Companies in Bangladesh

Abstract: "Bangladesh faces many ecological challenges, including air and water contamination, land degradation, and waste management". Bangladesh faces many ecological challenges, including air and water contamination, land degradation, and waste management. This study was designed to investigate the extent and nature of environmental accounting and reporting of listed banks in Bangladesh in 12 major categories. Information was collected from the annual reports of 20 banks listed on the Dhaka Stock Exchange for the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
98
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(116 citation statements)
references
References 51 publications
15
98
0
3
Order By: Relevance
“…Following previous research in the banking sector in emerging countries [38] it was found that disclosure of environmental information increased sharply from 16% in 2010 to 83% in 2014 in the financial sector in Bangladesh. In addition, authors reviewed Bangladesh Bank's recent fruitful initiatives on environmental disclosures, and the findings of the 12 categories had managerial implications for policy makers in corporations as well as the government.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous research in the banking sector in emerging countries [38] it was found that disclosure of environmental information increased sharply from 16% in 2010 to 83% in 2014 in the financial sector in Bangladesh. In addition, authors reviewed Bangladesh Bank's recent fruitful initiatives on environmental disclosures, and the findings of the 12 categories had managerial implications for policy makers in corporations as well as the government.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous investments in energy consumption and natural resource consumption, as well as manufacturing sectors and infrastructure, have had seriously harmful impacts on the environment [18]. Environmental accounting creates accountability for business entities in terms of their efforts to protect the environment in their corporate decisions [19]. Environmental accounting constitutes a tool for applying the sustainable development concept and now commands acceptance as a means of ensuring the preservation of the environment Environmental accounting information includes financial, environmental performance, and policy aspects, which are scattered in many parts of annual reports and social responsibility reports.…”
Section: Materials Flow Managementmentioning
confidence: 99%
“…Environmental accounting constitutes a tool for applying the sustainable development concept and now commands acceptance as a means of ensuring the preservation of the environment Environmental accounting information includes financial, environmental performance, and policy aspects, which are scattered in many parts of annual reports and social responsibility reports. The quality of disclosures can be characterized from aspects of comprehensiveness, reliability, and compliance (Masud, Bae, & Kim, 2017). In decision making, an organization considers different pressures from internal and external parties and attempts to legitimize the impact of its activities on the environment in the eyes of society and various pressure groups.…”
Section: Materials Flow Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Member states were obliged to incorporate the measure into the national legislation within a two-year period. On the basis of descriptions provided by various authors in their scientific works (M. A. K. Masud, S. M. Bae, & J. D. Kim, 2017 [11]; A.Venturelli, F. Caputo, S. Cosma, et al, 2017 [12]), it is possible to summarize the main reasons for compiling such reports: 1. Mandatory disclosure of financial and non-financial information relating to the environment protection and labour relations in the context of the annual report is based on the national legislation, eventually the EU Council Directive, namely 2014/95/EU of the European Parliament and of the Council, which came into force on 22 October 2014.…”
Section: Brief Literature Reviewmentioning
confidence: 99%